Evaluation of the marginal and internal gaps of three different dental prostheses: comparison of the silicone replica technique and three-dimensional superimposition analysis - Park, Jin-Young (J Adv Prosthodont, 2017)
PURPOSE: The purposes of this study were to evaluate the marginal and internal gaps, and the potential clinical applications of three different methods of dental prostheses fabrication, and to compare the prostheses prepared using the silicone replica technique (SRT) and those prepared using the three-dimensional superimposition analysis (3DSA). MATERIALS AND METHODS: Five Pekkton, lithium disilicate, and zirconia crowns were each manufactured and tested using both the SRT and the two-dimensional section of the 3DSA. The data were analyzed with the nonparametric version of a two-way analysis of variance using rank-transformed values and the Tukey's post-hoc test (α = .05). RESULTS: Significant differences were observed between the fabrication methods in the marginal gap (P < .010), deep chamfer (P < .001), axial wall (P < .001), and occlusal area (P < .001). A significant difference in the occlusal area was found between the two measurement methods (P < .030), whereas no significant differences were found in the marginal gap (P > .350), deep chamfer (P > .719), and axial wall (P > .150). As the 3DSA method is three-dimensional, it allows for the measurement of arbitrary points. CONCLUSION: All of the three fabrication methods are valid for measuring clinical objectives because they produced prostheses within the clinically acceptable range. Furthermore, a three-dimensional superimposition analysis verification method such as the silicone replica technique is also applicable in clinical settings.